2003
DOI: 10.1071/bt02113
|View full text |Cite
|
Sign up to set email alerts
|

Salinisation and prospects for biodiversity in rivers and wetlands of south-west Western Australia

Abstract: Saline water was common in south-west Western Australian aquatic systems prior to land-clearing because most streams and wetlands were ephemeral and evapo-concentrated as they dried, and there were high concentrations of stored salt in groundwater and soil profiles. Nevertheless, a 1998 review of salinity trends in rivers of south-west Western Australia showed that 20-fold increases in salinity concentrations had occurred since clearing in the medium-rainfall zone (300–700 mm). More recent data confirm these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 50 publications
2
112
2
Order By: Relevance
“…However, since 1975, a climatic phase shift has seen significant reductions in rainfall and stream flows (Table 1) (CSIRO 2009a). Furthermore, 80-90% of native vegetation has been cleared for agriculture (Halse et al 2003), resulting in .70% of the Australian continent's secondary salinised areas. Now only ,44% of flow in the largest 30 rivers is fresh (Mayer et al 2005).…”
Section: South-western Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, since 1975, a climatic phase shift has seen significant reductions in rainfall and stream flows (Table 1) (CSIRO 2009a). Furthermore, 80-90% of native vegetation has been cleared for agriculture (Halse et al 2003), resulting in .70% of the Australian continent's secondary salinised areas. Now only ,44% of flow in the largest 30 rivers is fresh (Mayer et al 2005).…”
Section: South-western Australiamentioning
confidence: 99%
“…These current stressors have already caused reductions in the range of aquatic fauna from upstream areas of catchments (e.g. Morgan et al 1998;Halse et al 2003;Davies 2010) and the greatest diversity of freshwater fishes is now found in less-degraded, forested systems (Morgan et al 1998).…”
Section: South-western Australiamentioning
confidence: 99%
“…Anthropogenic (secondary) salinisation of arid and Mediterranean lands occurs globally and influences the distribution of aquatic assemblages across the landscape (Roberts & Irving-Bell, 1997;Halse et al, 2003;Hart & Lovvorn, 2005;Pinder et al, 2005;Piscart et al, 2005b). General consensus exists that increasing river and wetland salinity has potential to cause local extinctions, alterations in ecosystem function and extensive environmental damage (Halse et al, 2003;Kefford et al, 2003;Jardine et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic (secondary) salinisation of arid and Mediterranean lands occurs globally and influences the distribution of aquatic assemblages across the landscape (Roberts & Irving-Bell, 1997;Halse et al, 2003;Hart & Lovvorn, 2005;Pinder et al, 2005;Piscart et al, 2005b). General consensus exists that increasing river and wetland salinity has potential to cause local extinctions, alterations in ecosystem function and extensive environmental damage (Halse et al, 2003;Kefford et al, 2003;Jardine et al, 2007). Halse et al (2003) predicted that approximately one-third of aquatic invertebrate diversity in the inland southwest of Western Australia (WA) will disappear with the expansion of secondary salinisation, and Pinder et al (2005) suggested that up to 100 species that are largely restricted to the inland southwest are at risk of extinction.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, secondary salinisation is principally caused by rising watertables as a consequence of reduced evapotranspiration following changes in land use, typically land clearing for agriculture. The south-west corner of Australia, where~80-90% of the land has been cleared, is a hot spot in terms of secondary salinisation (NLWRA 2001;Halse et al 2003;Pinder et al 2004). As a result, most of the freshwater ecosystems in south-western Australia are affected by increasing salinity, with 56% having become brackish (1.0-2.0 g L -1 ) or saline (>2.0 g L -1 ) (see Mayer et al 2005).…”
Section: Salinity As a Threatening Processmentioning
confidence: 99%